1992
DOI: 10.1093/jn/122.suppl_3.728
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Trial of Beta-Carotene in Subjects Infected with the Human Immunodeficiency Virus ,

Abstract: beta-Carotene is a nontoxic carotenoid with immunomodulating properties in animals and humans. Based on our observations in normal immunocompetent subjects, we studied the effects of this compound in 11 patients infected with the human immunodeficiency virus (HIV). Each subject received 60 mg of beta-carotene daily for 4 mo. Clinical and laboratory studies were obtained at baseline, every month while on treatment and for 2 mo after treatment. Increases in the percent of cells expressing Leu 11 (natural killer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…The results from the studies of disease groups should be interpreted with care, bearing in mind the dif®culty in controlling these trials adequately. This may account for the increase in the percentage NK cells at 3 months, but not at 4 months in an uncontrolled b-carotene supplementation trial of HIV patients (Garewal et al, 1992). The controlled studies in healthy volunteers that do report a positive effect of b-carotene on lymphocyte subsets, also contain some anomalous ®ndings.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The results from the studies of disease groups should be interpreted with care, bearing in mind the dif®culty in controlling these trials adequately. This may account for the increase in the percentage NK cells at 3 months, but not at 4 months in an uncontrolled b-carotene supplementation trial of HIV patients (Garewal et al, 1992). The controlled studies in healthy volunteers that do report a positive effect of b-carotene on lymphocyte subsets, also contain some anomalous ®ndings.…”
Section: Discussionmentioning
confidence: 96%
“…In human studies, van Poppel et al (1993) reported an increase in lymphocyte proliferation in PHA-stimulated cultures but not in Con A-stimulated cultures following dietary supplementation with 20 mg b-carotene daily for 14 weeks. b-Carotene, or vitamin C, depletion ± repletion studies have failed to show an effect on lymphocyte proliferation in response in healthy volunteers (Jacob et al, 1991;Daudu et al, 1994) and immunocompromised groups also fail to show consistent improvements in lymphocyte proliferation in response to supplementation (Garewal et al, 1992;Zhang et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In non-controlled trials of ␤-carotene supplementation, the proportion of NK cells was significantly increased from baseline after supplementation in patients with oral leukoplakia (N ϭ 16; 40 mg/d for 6 months), 115 but not in HIV-positive patients (N ϭ 11; 60 mg/d for 4 months) 116 or in healthy adult women (N ϭ 9; 15 mg/d for 28 days). 117 RCTs have shown little effect of supplementation with ␤-carotene on the proportion or absolute number of circulating NK cells in several populations (Table 3; .…”
Section: Distribution Of Cell Typesmentioning
confidence: 99%
“…In small studies, b-carotene supplementation of HIV-seropositive individuals has no conclusive effect on viral load and immune cell subsets (Garewal et al, 1992;Coodley et al, 1993bCoodley et al, , 1996Silverman et al, 1994;Fryburg et al, 1995;Nimmagadda et al, 1998). b-Carotene supplementation alleviates acquired immunodeficiency syndrome (AIDS)-related and erythropoietic protoporphyria-related symptoms (Bianchi-Santamaria et al, 1992;Mathews-Roth, 2000), and may reduce pregnancy-related mortality in combination with vitamin A (West et al, 1999).…”
Section: Introductionmentioning
confidence: 99%